Factors predicting axial spondyloarthritis among first-degree relatives of probands with ankylosing spondylitis: a family study spanning 35 years. Issue 6 (11th March 2022) - van der Linden, Sjef M; Khan, Muhammad Asim; Li, Zhixiu; Baumberger, Heinz; Zandwijk, Hermine van; Khan, Kazim; Villiger, Peter M; Brown, Matthew A
Abstract : Objective: Factors predicting axial spondyloarthritis (axSpA) among first-degree relatives (FDRs) of ankylosing spondylitis (AS) patients need to be defined. We investigated the predictive value of the probands' HLA-B27 and radiographic sacroiliitis status on disease occurrence among their FDR. We also assessed the predictive value of features of the clinical history, including chronic inflammatory back pain (CIBP) and acute anterior uveitis (AAU), among the FDR and how they can be used to improve classification and diagnosis of axSpA. Methods: In 1985, we studied 363 AS probands and 806 FDR who underwent rheumatologic examination, completed questionnaires, provided blood samples for HLA-typing and underwent radiography of sacroiliac joints. At follow-up in 2018–2019, 125 patients and 360 FDR were available for study, and completed a postal questionnaire about axSpA features. FDRs were asked to report whether after 1985 they had been diagnosed by Swiss rheumatologists as having axSpA. Results: Among HLA-B27(+) FDR, axSpA occurred in 25.4%–26.3%, independent of the radiographic sacroiliitis status of the proband. AAU occurred in 13/34 (38.2%) FDR with axSpA vs 29/251 (11.6%) FDR without axSpA (p = 0.00004, OR=4.74 95% CI 2.15 to 10.47). The presence of CIBP at baseline did not predict later occurrence of axSpA but combining CIBP and pain/discomfort at the thoracic spine and at anterior (ventral) chest wall ever, assessed at follow-up in 2018–2019, provided 83.1% sensitivity and 87.2% specificity for current axSpA. Conclusion: Occurrence of AAU among FDR of axSpA probands should prompt screening for axSpA. Moreover, co-occurrence of CIBP and pain/discomfort in the thoracic spine and at anterior chest wall as a three-question tool may further enhance clinical suspicion of axSpA among these FDR.